Differentiated Education through Hybrid Learning Environments in Teaching and Learning of Mathematics (Docentes 2.0 Journal, 2024)
Students are immersed in a digital age, so much of their time is spent using electronic devices, playing games, messaging, and social networks. This essay was framed under the inductive method in the humanistic paradigm, with a qualitative, interpretive approach and topical narrative design to reflect on the importance of implementing differentiated education in teaching. They are learning mathematics through hybrid learning environments, aiming to improve the quality of mathematics education, adapting it to students' individual needs, and taking advantage of the advantages of technology. In this sense, the historical and research background and conceptual bases of applying a differentiated education approach in mathematics through hybrid environments are presented. This combination offers a promising approach to addressing the changing needs of students through flexible spaces in an increasingly digital and diverse world.
Keywords: Differentiated education; hybrid learning environments; mathematics education